Analysis Of Consumer Loyalty Improvement Strategy Through Customer Experience And Customer Satisfaction As A Competitive Advantage For Saff & Co Perfume - Anggit Dyah Kusumastuti; Daffa Fauzan Nugroho; Febrianto Saputra; Meitri Wulandari Djaya Negara; Akbar Zukhruf Maytatu (Asosiasi Dosen Muda Indonesia, 2025)
This study analyzes strategies to strengthen the market position of a brand, namely Saff & Co. perfume. The urgency of this research is because the increasingly competitive perfume industry demands a deep understanding of the determinants of customer loyalty. Analysis of customer experience and customer satisfaction is crucial because both not only have a direct impact on loyalty, but also play a role as a strategic asset in creating a sustainable competitive advantage for Saff & Co. Perfume. The purpose of this study is to analyze strategies to increase consumer loyalty by examining the influence of customer experience on customer satisfaction, as well as the role of satisfaction in building loyalty, in order to formulate a competitive advantage. This research method uses a literature study method (qualitative) with content analysis techniques.